Acute Liver Infarct with a Superimposed Liver Abscess as a Consequence of Hypercoagulable State in a Patient with COVID-19 without Respiratory Manifestations - Rivera-Cariño, Patricia Jenny; Rosa-Cortés, Pedro; Llopart-Herrera, Liliana; Acosta-Pumarejo, Eduardo; Rey-Mejías, Luis; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2023)
COVID-19 infection has been associated, particularly in severely ill patients requiring hospitalization, with a hypercoagulable state. The case presented herein was a 66-year-old man with SARS-CoV-2 infection who did not have any respiratory symptoms. He presented with the following clinical manifestations: portal vein and hepatic artery thrombosis, liver infarction, and a superimposed abscess of the liver. In this case, early detection and the administration of anticoagulants and antibiotics led to a significant improvement within weeks of the diagnosis. We encourage physicians to be aware of COVID-19–associated hypercoagulable state and its potential complications, regardless of the acuity of the presentation or the absence of respiratory symptoms.